Patriarhul Avraam – Etalon de credinţă pentru creştini (Rm 4, 17-25) - Tușa-Pașca, Stelian (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2019)
The patriarch Abraham is a unique character in the history of the Old Testament. Considering the blessing he was offered by God, he was considered a landmark of faith and faithfulness by both Jews, Christians and Muslims. For Jews, the Abrahamic lineage is essential for through it they become sons of oath. Islamist also consider themselves heirs of the Abrahamic promise as they are sons of Ismael, the Abraham’s firstborn. In what Christianity is concerned, Abraham is perceived as a paradigm for one’s submission and obedience to God as well as a landmark for faithfulness for every Christian. The Christian interpretation of Abraham is a spiritual one. The ideas Jesus Christ evoked in His disputes with Jews regarding patriarch Abraham, have been assumed by the Apostles and redirected in many ways and perspectives. In the present research I aim to present the way Saint Paul regarded and perceived Patriarch Abraham in the Epistle to Romans, chapter 4, verses 17-25. In my endeavor, besides the Pauline background of the matter, I will seek to emphasize and develop on the event described in Gen 15,1-6 which Saint Paul refers to directly, specifying the events prior to the moment the faith of Patriarch Abraham was considered by God righteousness.